Benzodiazepine hypnotics remain effective for 24 weeks. Issue 6319 (20th March 1982) - Oswald, I; French, C; Adam, K; Gilham, J
Abstract : Ninety-seven poor sleepers aged 40-68 years took capsules nightly for 32 weeks and made daily subjective ratings. The benzodiazepine hypnotics lormetazepam 2 mg and nitrazepam 5 mg appeared still to improve sleep after 24 weeks of intake when compared with continuous placebo intake. The sustained effectiveness was most evident in a significant shortening of the time taken to fall asleep in patients receiving lormetazepam. After weeks, sleep latency and the quality of sleep were significantly worse than baseline values. The impairment was maximal on the second night after withdrawal of lormetazepam and on the fourth night after withdrawal of nitrazepam. It is concluded that benzodiazepines remain effective for at least 24 weeks but that a period of disturbed sleep may be expected after withdrawal.